The impacts of microcredit on poverty reduction evidence from Cambodian rural villages - Runsinarith, Phim (The Philippine review of economics, 2014)
This paper attempts to assess the poverty impact of microcredit for a panel of 827 households surveyed in 2001, 2004, and 2008 using propensity score matching (PSM) and the difference-in-difference (DID) method. The result shows that the poverty headcount in the microfinance institution (MFI) sample, which was highest in 2001, dropped faster compared to those in two other samples. This finding suggests that using loans from MFIs may have a positive effect on poverty reduction.